Welcome to Veterinary Medicine: Research and Reports - Musser JMB (Dove Medical Press, 2011)
Musser Jeffrey MBDepartment of Veterinary Pathobiology, College of Veterinary Medicine, Texas A&M University, TX, USAThis year marks the 250th anniversary of the Royal Veterinary School in Lyon, France, the world's first veterinary college. Since its inception, many changes have occurred in veterinary medicine such as views on education and didactic learning, demographics of our profession, and standards of practice in animal husbandry, medicine, surgery, anesthesia, and vaccinology. In fact, the concept of infectious diseases has changed - remember the germ theory was proposed a mere 140 years ago. However, one constant tenet in our profession has been the need to disseminate progresses, innovations, advances, and developments in veterinary sciences. Published reports are the foundation for the growth of medicine and science. What would the state of medicine be if Pasteur, Koch, Bourgelat, or Theobald Smith had not published their works?